Changes in hypertension prevalence, awareness, treatment, and control rates in Turkey from 2003 to 2012. Issue 6 (June 2016) - Sengul, Sule; Akpolat, Tekin; Erdem, Yunus; Derici, Ulver; Arici, Mustafa; Sindel, Sukru; Karatan, Oktay; Turgan, Cetin; Hasanoglu, Enver; Caglar, Sali; Erturk, Sehsuvar
Abstract : Objectives: The study aimed to assess the current epidemiology of hypertension, including its prevalence, the awareness of the condition and its treatment and control, in Turkey to evaluate changes in these factors over the last 10 years by comparing the results with the prevalence, awareness, treatment, and control of hypertension in Turkey (PatenT) study data (2003), as well as to assess parameters affecting awareness and the control of hypertension. Methods: The PatenT 2 study was conducted on a representative sample of the Turkish adult population ( n = 5437) in 2012. Specifically trained staff performed the data collection. Hypertension was defined as mean SBP or DBP at least 140/90 mmHg, previously diagnosed disease or the use of antihypertensive medication. Awareness and treatment were assessed by self-reporting, and control was defined as SBP/DBP less than 140/90 mmHg. Results: Although the prevalence of hypertension in the PatenT and PatenT 2 surveys was stable at approximately 30%, hypertension awareness, treatment, and control rates have improved in Turkey. Overall, 54.7% of hypertensive patients were aware of their diagnosis in 2012 compared with 40.7% in 2003. The hypertension treatment rate increased from 31.1% in 2003 to 47.4% in 2012, and the control rate in hypertensives increased from 8.1% in 2003 to 28.7% in 2012. The rate of hypertension control in treated patients improved between 2003 (20.7%) and 2012 (53.9%). Awareness of hypertension was positively associated with older age, being a woman, residing in an urban area, a history of parental hypertension, being a nonsmoker, admittance by a physician, presence of diabetes mellitus, and being obese or overweight; it was inversely associated with a higher amount of daily bread consumption. Factors associated with better control of hypertension were younger age, female sex, residing in an urban area, and higher education level in Turkey. Conclusion: Although some progress has been made in recognizing hypertension from 2003 to 2012, there is still a large population of untreated or inadequately treated hypertensives in Turkey. Strengthening of population-based efforts to improve the prevention, early detection, and treatment of hypertension is needed. Abstract : Supplemental Digital Content is available in the text